2017
DOI: 10.1155/2017/4724302
|View full text |Cite
|
Sign up to set email alerts
|

Optimising the Performance of Cement-Based Batteries

Abstract: The development of a battery using different cement-based electrolytes to provide a low but potentially sustainable source of electricity is described. The current, voltage, and lifespan of batteries produced using different electrolyte additives, copper plate cathodes, and (usually) aluminium plate anodes were compared to identify the optimum design, components, and proportions to increase power output and longevity. Parameters examined include water/cement ratio, anode to cathode surface area ratio, electrod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…When the alkaline concentration was 10M KOH, at W/S = 0.4 to 0.6, the discharge curve showed an excellent performance at W/S = 0.6 due to an increased connectivity and greater volume of pores. 16 The maximum operating voltage of GP was 1.17 V at W/S = 0.6, lower than the value of 1.38 V at W/C = 0.5 under discharge at 0.13 mAcm −2 . The presence of an alkali (KOH) in GP accelerated the corrosion of aluminum and greatly increased the over-potential for electro-dissolution, 45 but the hydration alkaline product of OPC, Ca(OH) 2 , was only slightly soluble in water, which limited the corrosive action on the aluminum material.…”
Section: Gp-based and Opc-based Battery Discharge Performance At Diff...mentioning
confidence: 71%
See 1 more Smart Citation
“…When the alkaline concentration was 10M KOH, at W/S = 0.4 to 0.6, the discharge curve showed an excellent performance at W/S = 0.6 due to an increased connectivity and greater volume of pores. 16 The maximum operating voltage of GP was 1.17 V at W/S = 0.6, lower than the value of 1.38 V at W/C = 0.5 under discharge at 0.13 mAcm −2 . The presence of an alkali (KOH) in GP accelerated the corrosion of aluminum and greatly increased the over-potential for electro-dissolution, 45 but the hydration alkaline product of OPC, Ca(OH) 2 , was only slightly soluble in water, which limited the corrosive action on the aluminum material.…”
Section: Gp-based and Opc-based Battery Discharge Performance At Diff...mentioning
confidence: 71%
“…Rampradheep et al 14 used a self-curing agent (polyethylene glycol) that enhanced the cement past moisture to produce a maximum voltage of 0.6 V. Holmes et al 15 added carbon fibers and nanotubes to the electrolyte layers, resulting in a maximum voltage of 0.7 V and a current density of 35.21 μAcm −2 . Byrne et al 16 used a magnesium plate as the anode, a copper plate as the cathode, and cement with a high water content, carbon black, plasticizer, salts, and silica fume as the electrolyte. This cell produced an open-circuit voltage of 1.55 V, a maximum current over 4 mA under a 10 resistor, and a steady current of 0.59 mA with a lifespan of over 21 days.…”
mentioning
confidence: 99%
“…Other combinations of electrode materials, conductive fillers, and different water-cement ratios (w/c) were investigated as well. Byrne et al [12] found that the optimal electrode materials were magnesium anode and copper cathode in their study, and they concluded that increasing the w/c ratio could slightly increase the current output but had no effect on prolonging the lifespan. Their battery had an initial peak current of 4.37 mA (over a 10 Ω resistor) and a duration of 12 h (measured when current was great than 0.59 mA).…”
Section: Introductionmentioning
confidence: 97%
“…In the present study, the effect of MgSO4 salt concentration were studied based on conductivity and transport properties of a new type of solid polymer electrolyte film in which the corn starch is complexed with magnesium sulfate (Starch-MgSO4 system). The picking of the MgSO4 salt is principally because of its ready accessibility, lesser harmfulness, and high potential in electrochemical applications (Byrne et al, 2017;van Essen et al, 2009;Wang et al, 2017;Masse et al, 2015;Lota et al, 2013;Hongois et al, 2011;Zhu et al, 2018;Mahon et al, 2017).…”
Section: Introductionmentioning
confidence: 99%